(untitled) (Лучшие интеллектуальные исследования, 2025)
Annotatsiya. Ushbu tadqiqot Namangan viloyati moliyaviy boshqaruvidagi risklarni tahlil qilish va ularni kamaytirish strategiyalarini ishlab chiqishga qaratilgan. Maqolada 2020-2023 yillardagi byudjet hisobotlari, soliq statistikasi va xalqaro tajribalar tahlil qilinadi. Tadqiqot natijalari shuni ko’rsatadiki, viloyat byudjetining 68% transfertlar hisobiga to’ldirilishi moliyaviy barqarorlik uchun jiddiy risk hisoblanadi. Ishlab chiqilgan strategiyalar orasida soliq bazasini kengaytirish, iqtisodiy diversifikatsiya va xavfsizlik fondini tashkil etish kabi choralar muhim o’rin tutadi. Annotation. This study examines risk analysis and mitigation strategies in public financial management, focusing on the Namangan region of Uzbekistan. The research analyzes budget reports (2020-2023), tax statistics, and international best practices to identify key financial risks, particularly the region’s heavy reliance on central budget transfers (68%). The proposed strategies include expanding the local tax base, economic diversification through industrial zones (e.g., "Namangan Agro"), and establishing a financial safety net. Methodologically, the study employs correlation analysis, dynamic trend assessment, and expert evaluations. The findings suggest that implementing tax incentives for SMEs, attracting foreign investment, and adopting modern monitoring systems (e.g., blockchain-based transparency tools) can reduce fiscal dependency and enhance economic resilience. The research contributes to both theoretical frameworks in fiscal decentralization and practical policy-making for regional financial stability in developing economies. Аннотация. Данное исследование посвящено анализу рисков и стратегиям их снижения в системе государственного финансового управления на примере Наманганской области Узбекистана. На основе бюджетных отчетов (2020–2023 гг.), налоговой статистики и международного опыта выявлены ключевые проблемы, включая высокую зависимость от трансфертов (68%). Предложены стратегии: расширение налоговой базы (льготы для МСП), диверсификация экономики (промзона «Namangan Agro») и создание резервного фонда. Методология включает корреляционный анализ, оценку динамики показателей и экспертные оценки. Результаты показывают, что внедрение налоговых стимулов, привлечение инвестиций в IT-сектор и цифровые инструменты мониторинга (например, блокчейн) могут сократить зависимость от трансфертов до 55% к 2027 году. Исследование имеет практическую ценность для регионов с аналогичными бюджетными рисками.